If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48x + -24 = 10x + 16 Reorder the terms: -24 + 48x = 10x + 16 Reorder the terms: -24 + 48x = 16 + 10x Solving -24 + 48x = 16 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -24 + 48x + -10x = 16 + 10x + -10x Combine like terms: 48x + -10x = 38x -24 + 38x = 16 + 10x + -10x Combine like terms: 10x + -10x = 0 -24 + 38x = 16 + 0 -24 + 38x = 16 Add '24' to each side of the equation. -24 + 24 + 38x = 16 + 24 Combine like terms: -24 + 24 = 0 0 + 38x = 16 + 24 38x = 16 + 24 Combine like terms: 16 + 24 = 40 38x = 40 Divide each side by '38'. x = 1.052631579 Simplifying x = 1.052631579
| 30(2x-1)=6(x+4)+3x | | x^2-3x+1.05=0 | | .8x-.6x=2 | | 95+78+39+x=65 | | .66x+.33x-6=1 | | .1x-1=0 | | 69x=-72 | | -13x+10=-16 | | 18x-6=-30 | | 5+3h=54 | | .33x-4=2 | | x-4/6=x/8 | | b^6=64 | | Y^4-50y^2+49=0 | | 5x^4+20x^3=0 | | 4b-6+b-9=0 | | 5y^2-35y=0 | | N^2-17n+72=0 | | 2m+5m-3=4 | | X^5-3x^4-6x^3+28x^2-24x=0 | | 15(t-3)+6t=7(3t+5)-9 | | 15b+2=42 | | 20x^2+4x-3=0 | | 15x^2-26x+11=0 | | 7y+2=-8y+1 | | y-39=-41 | | 3x(4-3y)+9y=12 | | 1T=15d+4 | | .06x^2=2.4x+0.6 | | 2(7x+4)=4x-7(2-x)+7 | | 8888=72 | | T=15(d)+4 |